Individual Student Strategies in Speaking Skill in Online Learning at Muhammadiyah University of Bengkulu - Fetriani Fetriani; Eki Saputra; Fiska Miadewi (Edumaspul: Jurnal Pendidikan, 2022)
The objective of this research is to know and describe about what are individual students strategies in speaking in online learning at Muhammadiyah University of Bengkulu. The design of this research was qualitative study because this research was conducted to know about what are individual students’ strategies in speaking in online learning at Muhammadiyah University of Bengkulu. The instruments of this research were video, questionnaire and interview. The result of this research is they used memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies, and social strategies.